Exploring technologies and challenges in English writing classes in a rural area by millennial lecturers - Rafita Tioria Sianipar; Mahmud Layan Hutasuhut (ELT Forum: Journal of English Language Teaching, 2024)
Research on the use of technology in English writing instructions has indeed been extensively conducted. However, studies examining the utilization of technology in writing classes by millennial lecturers in rural areas are still scarce. Hence, this research addresses the underexplored domain of technology integration in writing classes by millennial lecturers in colleges within a rural area, focusing on the types of technology used and associated challenges. Conducted in North Tapanuli, North Sumatra, Indonesia, the study involves six participants chosen through purposive sampling based on specific criteria. Data collection utilizes semi-structured interviews and open-ended questionnaires, employing thematic analysis for interpretation. Findings reveal eight technology categories employed by millennial English lecturers in a rural area, including social media, video conferencing platforms, AI-powered software, language learning apps, word-processing software, online creative platforms, email, and web-based publication. Challenges faced are categorized into student, lecturer, and university constraints, covering economic limitations, technological unfamiliarity, grading difficulties, professional development needs, and resource constraints. Overall, the study provides relevant contributions for educators, institutions, and policymakers striving to enhance technology integration in rural college areas, emphasizing inclusivity and effective learning environments.